Technological Change in the Retirement Transition and the Implications for Cybersecurity Vulnerability in Older Adults - Morrison, Benjamin A.; Coventry, Lynne; Briggs, Pam (Frontiers in Psychology, 2020)
Retirement is a major life transition, which leads to substantial changes across almost all aspects of day-to-day life. Although this transition has previously been seen as the normative marker for entry into older adulthood, its influence on later life has remained relatively unstudied in terms of technology use and cyber security behaviours. This is problematic as older adults are at particular risk of becoming victims of cyber-crime. This study aimed to investigate which factors associated with the retirement transition were likely to increase vulnerability to cyberattack in a sample of 12 UK adults, all of whom had retired within the past 5 years. Semi-structured, one to one interviews were conducted and subsequently analysed using thematic analysis. Six themes were identified referring to areas of loss in: Social Interaction, Finances, Day-to-Day Routine, Feelings of Competence, Sense of Purpose and Technology Support Structures. Each of these losses may lead to cybersecurity vulnerability and thus has implications for how we might build cyber resilience in retirees, with further implications for future research.